The fetomaternal outcome in case of post-dated pregnancy at tertiary care center - Chaudhari, Prachi; Vohra, Hafsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Post-date pregnancy is a challenge for maternal and perinatal care and a leading cause of neonatal morbidity and mortality. The aim of the present study was to analyse the risk factors and feto-maternal outcome of pregnancies which goes beyond due date. Method: It is a prospective study carried out during period from October 2021 to October 2022 in obstetrics and gynecology department of B. J. medical college and hospital, Ahmedabad. 100 cases of post-dated pregnancy out of 12,885 delivered cases were studied in this study. Results: The present study was conducted in the hospital for risk factors leads to post-dated pregnancy and maternal and neonatal morbidity and mortality. Among the 12,885 deliveries, 990 were post-dated pregnancy and 100 cases studied in this study. In the present study, incidence of post-dated pregnancy 7.6%. Majority of women belonged to age group 21 to 25 years (66%). 68% of them delivered vaginally, 32% women required caesarean section, the most common indication being foetal distress, 57% of women were given induction by various means and 32% of them had successful vaginal delivery.19% babies had NICU admission with respiratory distress (7%) being the most common reason. Conclusions: Post-dated pregnancy is high risk condition which is challenge to obstetrician and leads to maternal and neonatal complications. A better management is a pre-requisite to reduce the rate of perinatal mortality and morbidity in this group of patients. With regular antenatal check-up, the incidence of post-dated pregnancies can be decreased.